Análise exergética de uma planta termoelétrica abastecida com casca de arroz - Verhagen, Lucas (2021)
The present work has as objective a thermodynamic and economic analysis of the implantation energy in a Thermal Power Plant (TTP), using as fuel an agroindustrial residue that is the rice husk. The analysis is a thermoelectric in the State of Rio Grande do Sul, which is the largest rice producer in Brazil, with 7,866.9 ×103 tonnes of rice produced in the 2019/20 harvest. The plant in the present study has an electrical generation power of 5 MW, assuming that the biomass to supply this plant comes from Arrozeira Pelotas (2021). The methodology to be used in this analysis is through an exergetic analysis, based on Galante (2019), which in turn uses the methodology described in Bejan; Tsatsaronis; Moran (1995), as a basis. It also aims to attest to the feasibility of burning rice husks in a steam power cycle, Rankine cycle, with an analysis by the first law and second law of thermodynamics. The payback made for this 20-year-life plant resulted in a payback period of 8,53 years. All calculations were performed using the Python programming language.